Effect of Miyodo on Growth, Yield Attributes and Yield in T. Aman Rice cv. BR-11 - Sarwar, AKMG; Sultana, J; Islam, MO; Prodhan, AKMA (Progressive Agriculture, 2013)
An experiment was conducted in the field laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh, to investigate the effect of foliar application of Miyodo on morphology, yield contributing characters and yield of T. aman rice cv. BR-11. The concentrations of Miyodo used were 2 mgL-1, 3 mgL-1, 4 mgL-1 and 5mgL-1 with a control. The experiment was laid out in a randomized complete block design with three replications. Application of Miyodo by spraying at 45 days after transplanting significantly enhanced plant height, number of tillers and effective tillers, number of leaves and leaf area, size of flag leaf, total dry matter, panicle length, number of total grains and filled grains, 1000-grain weight, grain yield, straw yield, and harvest index. The result showed that the application of 5 mgL-1 Miyodo produced the highest grain yield of BR-11 compared to other concentrations as well as control. However, further study is needed to determine the higher concentration limit of Miyodo in maximizing the growth and yield of T. aman rice cv. BR-11. DOI: http://dx.doi.org/10.3329/pa.v19i1.17106 Progress. Agric. 19(1): 45 - 49, 2008